20th anniversary of service to the agricultural sector in Suriname 1982-2002 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This brochure is an homenage to the twenty years of dedicated and productive presence in Suriname of the Inter-American Institute for Cooperation on Agriculture (IICA).